2019
DOI: 10.1038/s41598-019-47500-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequencing reveals association of variants and haplogroup M33a2′3 with High altitude pulmonary edema susceptibility in Indian male lowlanders

Abstract: High Altitude Pulmonary Edema (HAPE) is a threatening disorder caused due to acute exposure to high altitude above 3000 m. Apart from multiple factors involved, the genetic factors also play an important function in the pathogenesis of HAPE. This study aims to evaluate the role of mtDNA polymorphism and their association with haplogroup in understanding the etiology of HAPE. In this study, all the HAPE susceptible and acclimatized control subjects could be classified into nine haplogroups pertaining mostly to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
(49 reference statements)
0
11
5
Order By: Relevance
“…Since, the biological effects of high altitude were observed at > 3000 m existence of these co-occurrence pairs seemed a possible combination of variants that affects mitochondrial bioenergetics. Variant 4491 of ND2 gene was found to be associated with high altitude pulmonary edema (HAPE) susceptible in low altitude population 46 whereas in our analysis, this variant was found to co-occur with 3394 and its exclusive presence in the higher altitude regions suggested its adaptive dependence. The variable sites forming the global connected nodes 9540 and 10873 were the ‘RSRS50’ ancestral variants 47 while 10400 and 16327 were markers of M sub-haplogroups 48 .…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Since, the biological effects of high altitude were observed at > 3000 m existence of these co-occurrence pairs seemed a possible combination of variants that affects mitochondrial bioenergetics. Variant 4491 of ND2 gene was found to be associated with high altitude pulmonary edema (HAPE) susceptible in low altitude population 46 whereas in our analysis, this variant was found to co-occur with 3394 and its exclusive presence in the higher altitude regions suggested its adaptive dependence. The variable sites forming the global connected nodes 9540 and 10873 were the ‘RSRS50’ ancestral variants 47 while 10400 and 16327 were markers of M sub-haplogroups 48 .…”
Section: Discussioncontrasting
confidence: 59%
“…As the efficiency of the electron transport chain governs key aspects of aerobic energy metabolism 51 , several investigators have suggested that functional modifications of redox proteins, such as cytochrome b, may be involved in physiological adaptation to different thermal environments 26,27,52 . It is interesting to note that variants located in CYB gene (such as C14766T) are known to be significantly higher in the high-altitude pulmonary edema a disorder arising due to acute exposure to high altitude above 3000 m and it has been hypothesized to play a role in high altitude sickness 46 . The formation of local co-occurrence pairs and similarity clustering divided the altitude groups into the higher and the lower altitude regions.…”
Section: Discussionmentioning
confidence: 99%
“…Since, the biological effects of high altitude were observed at >3000 m existence of these co-occurrence pairs seemed a possible combination of variants that affects mitochondrial bioenergetics. Variant 4491 of ND2 gene was found to be associated with high altitude pulmonary edema (HAPE) susceptible in low altitude population [46] whereas in our analysis, this variant was found to co-occur with 3394 and its exclusive presence in the higher altitude regions suggested its adaptive dependence. The variable sites forming the global connected nodes 9540 and 10873 were the 'RSRS50' ancestral variants [47] while 10400 and 16327 were markers of M sub-haplogroups [46].…”
Section: Discussioncontrasting
confidence: 59%
“…Variant 4491 of ND2 gene was found to be associated with high altitude pulmonary edema (HAPE) susceptible in low altitude population [46] whereas in our analysis, this variant was found to co-occur with 3394 and its exclusive presence in the higher altitude regions suggested its adaptive dependence. The variable sites forming the global connected nodes 9540 and 10873 were the 'RSRS50' ancestral variants [47] while 10400 and 16327 were markers of M sub-haplogroups [46]. The markers 9540 and 10873 were found to be present throughout the human population, 10400 was known to be specific to Asian population and 16327 was known to be the marker of C sub-haplogroup of M haplogroup which was specific to Siberian and American regions.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation